Complex Arbitrations Multi-party, Multi-contract and Multi-issue. - Hanotiau, Bernard (International arbitration law library ;, 2020)
Complex Arbitrations: Multi-party, Multi-contract and Multi-issue' is a fully updated and renewed second edition of the far-sighted 2006 guide that was extensively used and much appreciated worldwide. Arbitrations which involve two or more parties and complex multi-party issues are becoming very common and frequent year by year. This one-stop guide provides a comprehensive and unique in-depth analysis of the multiplicity of issues arising from multi-party and multi-contract arbitration. It includes the decisions of several hundreds of courts from all major arbitral jurisdictions in the world and ad hoc and institutional awards ? published and unpublished ? rendered in all parts of the world under the auspices of all leading institutions.